SIPEDE: Enhancing e-Government Efficiency. - Wulandari, Ike Rahma; Choiriyah, Ilmi Usrotin (Indonesian Journal of Public Policy Review, 2024)
This research employs a qualitative descriptive method to assess the effectiveness of e-Government through the Village Apparatures Information System (SIPEDE) in Sidoarjo Regency. Utilizing observation, interviews, and documentation, both primary and secondary data reveal that the SIPEDE web application is maximally utilized by village officials. While the accuracy of program objectives and program socialization demonstrate success, challenges persist, including imperfect program utilization due to operational limitations. However, effective alignment with goals and regular online monitoring through a WhatsApp group indicate overall positive outcomes. The study underscores the significance of SIPEDE in enhancing information accessibility for the Department of Community and Village Empowerment. Highlight : Maximized Utilization: The research highlights the successful and maximized use of the SIPEDE web application by village officials in Sidoarjo Regency, emphasizing the positive impact on e-Government implementation. Challenges and Constraints: Despite overall effectiveness, the study identifies challenges such as imperfect program utilization due to operational limitations, emphasizing the need for continuous improvement and support for village officials. Strategic Information Alignment: The SIPEDE web application strategically aligns with the goals of the Department of Community and Village Empowerment, providing valuable information about village devices and contributing to the enhancement of e-Government initiatives. Keywords: e-Government, SIPEDE, Effectiveness, Village Officials, Information Accessibility